Egg Consumption and Incidence of Heart Failure: A Meta-Analysis of Prospective Cohort Studies - Khawaja, Owais; Singh, Hemindermeet; Luni, Faraz; Kabour, Ameer; Ali, Syed S.; Taleb, Mohammed; Ahmed, Hafeezuddin; Gaziano, John Michael; Djoussé, Luc (Frontiers in Nutrition, 2017)
Introduction Heart failure (HF) remains a major health problem affecting 5.7 million adults in USA. Data on the association of egg consumption with incident HF have been inconsistent. We, therefore, conducted this meta-analysis of prospective cohort studies to assess the relation of egg consumption with incident HF in the general population. Methods Using extensive online search, we conducted a meta-analysis of new onset HF following exposure to egg consumption. A random effects model was used and between studies heterogeneity was estimated with I2. Publication bias was assessed graphically using a funnel plot. All analyses were performed with Comprehensive Meta-Analysis (version 2.2.064). Results We identified four prospective cohorts for a total of 105,999 subjects and 5,059 cases of new onset HF. When comparing the highest (≥1/day) to the lowest category of egg consumption, pooled relative risk of HF was 1.25 (95% confidence interval = 1.12–1.39; p = 0.00). There was no evidence for heterogeneity (I2 = 0%) nor publication bias. On sensitivity analysis, stratification by gender differences, follow-up duration, and region where study was conducted did not alter the main conclusion. Conclusion Our meta-analysis suggests an elevated risk of incident HF with frequent egg consumption.